INVESTMENT CAN MODERATE THE EFFECT OF ZAKAT ON ECONOMIC GROWTH - Taufik Ibnu Karim; Ludfi Ludfi; Putri Nur Baiti; Khairil Anas; Jaenudin Jaenudin (JURNAL ILMIAH EDUNOMIKA, 2024)
ABSTRACT This research is a quantitative study with an explanatory approach. The data used in this study were obtained from credible data and of course also respondents who were responsible for the questions asked. The data were analyzed using the smart PL 4.0 analysis tool as the hypothesis below. Th result in this article show that the researcher built from the introduction and formulated in the research methodology section can be proven. This is because the P-Values in this article point towards a positive relationship and have a significant effect because the P-Values point towards positive and are below the significance level of 0.05, namely 0.002. In the next row, the second hypothesis of the third table in this article can be proven because of the same thing, namely the P-Values point towards positive and are below the significance level of 0.05, namely 0.000, which is more significant than direct testing of 0.002.. Thus, the first and second hypotheses in this article can be accepted. Keywords: Investation, Economic Growth, Zakat